#Whatwouldmagufulido? Kenya's digital "practices" and "individuation" as a (non)political act. Issue 1 (2nd January 2019) - Ogola, George
ABSTRACT: The ubiquity of new media technologies in many parts of Africa today and the celebratory narratives with which their adoption is routinely discussed in the continent often firmly silence some important questions. Among these is new media technologies' inherent capacity to also exclude, neuter or appropriate "popular" voices. This article attempts to explore this paradox. Focusing on Web 2.0 applications, more specifically Twitter, and using Kenya as a case study, the article explores the emergent expressive cultures new media technologies have incubated in the country. It argues that they "disrupt" the "normal" thus creating important pockets of "indiscipline" which variously challenge and confront power, and very often from the margins- but only partly. For while digital technologies enable and encourage public participation in "popular" conversations about self, community and nation through practices such as "individuation", the article also explores how these possibilities are constrained by problematic material conditions that render claims of popular inclusion and participation in these digital spaces fundamentally tenuous.